THE INFLUENCE OF MILAN ON THE DEVELOPMENT OF THE LOMBARD KOINÉ IN FIFTEENTH-CENTURY ITALY: THE LETTERS OF ELISABETTA OF PAVIA. - BROWN, JOSH (Quaderni d'italianistica, 2017)
The main tendency characterizing the development of language in Lombardy in the fourteenth and fifteenth centuries is the formation of a koiné. The extent to which Milan influenced the Lombard koiné is the subject of ongoing debate. On the one hand, scholars suggest that Milan provided a centralizing force for the "Milanization" of other Lombard vernaculars, similar to what occurred for Piedmont and the Veneto. On the other hand, studies have pointed out that Milan was not a centralizing force for the Lombard koiné and that it remains to be verified whether the prestige of Milanese influenced non-Milanese vernaculars. This paper looks at the extent to which Milan influenced the koiné in fifteenth-century Lombardy. I consider eight linguistic items, previously described as unique to the vernacular of Pavia, to verify their presence or absence in a corpus of religious writings from the fifteenth-century nun Elisabetta of Pavia and whether Milanese items can be identified. I consider aspects of phonology and morphology in Elisabetta's letters and conclude that her language is best characterized as a pre-koiné. The article concludes by arguing for less emphasis on the role of Milan in histories of the vernacular in Lombardy. This finding has implications for the history of non-literary writing in northern Italy and the importance attributed to capital cities in processes of koineization.